Proceedings of the IV International Research Conference "Information Technologies in Science, Management, Social Sphere and Med 2017
DOI: 10.2991/itsmssm-17.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Determinacy Analysis of Weights as Mathematical Basis of the Future Sociology

Abstract: Abstract-The mathematical method for processing data of a sociological survey is considered, taking into account the significance of respondents' opinions. Similarly to the S.V.Chesnokov's determinacy analysis (DA) of frequencies, a determinacy analysis of weights (DAW) is constructed in which the intensities and capacities of determinations are calculated by other formulas that allow taking into account the knowledge, life experience and professionalism of the respondent in the subject area.Keywords-determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the ESS study, interviewers are sent (to respondents) depending on their area of residence (to reduce travel costs), this factor and other characteristics of the interviewer (such as experience, personality traits, extraversion) has a decisive influence on the consent of the respondent. The results of research conducted by R. Groves [9] showed that in addition to the characteristics of the interviewer (the probability of agreement increases with increasing experience of the interviewer) such factors as the region of residence of the respondent, population density, socio-economic situation, ethnic group, religion and characteristics of housing have a significant influence, optimization of the process of recruiting respondents is especially relevant in the context of the study of weighing the opinions of respondents in accordance with their professional status, education experience [10]. J. Shinn [11] concludes that the characteristics of the area (number of apartments and population density) are also predictors of lack of response.…”
Section: Analysis Of Current Research and Publicationsmentioning
confidence: 99%
“…In the ESS study, interviewers are sent (to respondents) depending on their area of residence (to reduce travel costs), this factor and other characteristics of the interviewer (such as experience, personality traits, extraversion) has a decisive influence on the consent of the respondent. The results of research conducted by R. Groves [9] showed that in addition to the characteristics of the interviewer (the probability of agreement increases with increasing experience of the interviewer) such factors as the region of residence of the respondent, population density, socio-economic situation, ethnic group, religion and characteristics of housing have a significant influence, optimization of the process of recruiting respondents is especially relevant in the context of the study of weighing the opinions of respondents in accordance with their professional status, education experience [10]. J. Shinn [11] concludes that the characteristics of the area (number of apartments and population density) are also predictors of lack of response.…”
Section: Analysis Of Current Research and Publicationsmentioning
confidence: 99%